Migraine diagnosis and treatment: A knowledge and needs assessment of women's healthcare providers. Issue 1 (30th December 2020) - Verhaak, Allison M. S.; Williamson, Anne; Johnson, Amy; Murphy, Andrea; Saidel, Matthew; Chua, Abigail L.; Minen, Mia; Grosberg, Brian M.
Abstract: Background: Studies suggest that migraine is often underdiagnosed and inadequately treated in the primary care setting, despite many patients relying on their primary care provider (PCP) to manage their migraine. Many women consider their women's healthcare provider to be their PCP, yet very little is known about migraine knowledge and practice patterns in the women's healthcare setting. Objective: The objective of this study was to assess women's healthcare providers' knowledge and needs regarding migraine diagnosis and treatment. Methods: The comprehensive survey assessing migraine knowledge originally developed for PCPs was used in this study, with the addition of a section regarding the use of hormonal medications in patients impacted by migraine. Surveys were distributed online, and primarily descriptive analyses were performed. Results: The online survey was completed by 115 women's healthcare providers (response rate 28.6%; 115/402), who estimated that they serve as PCPs for approximately one‐third of their patients. Results suggest that women's healthcare providers generally recognize the prevalence of migraine, but experience some knowledge gaps regarding migraine management. Despite 82.6% (95/115) of survey respondents feeling very comfortable or somewhat comfortable with diagnosing migraine, only 57.9% (66/114) reported routinely asking patients about headaches during annual visits. Very few were familiar with the American Academy of Neurology guidelines on preventative treatment (6.3%; 7/111) and the Choosing Wisely Campaign recommendations on migraine treatment (17.3%; 19/110), and many prescribed medications known to contribute to medication overuse headache. In addition, only 24.3% (28/115) would order imaging for a new type of headache, 35.7% (41/115) for worsening headache, and 47.8% (55/115) for headache with neurologic symptoms; respondents cited greater tendency with sending patients to an emergency department for the same symptoms. Respondents had limited knowledge of evidence‐based, non‐pharmacological treatments for migraine (i.e., biofeedback or cognitive behavioral therapy), with nearly none placing referrals for these services. Most providers were comfortable prescribing hormonal contraception (mainly progesterone only) to women with migraine without aura (80.9%; 89/110) and with aura (72.5%; 79/109), and followed American College of Obstetricians and Gynecologists (ACOG) guidelines to limit combination hormonal contraception for patients with aura. When queried, 6.3% or less (5/79) of providers would prescribe estrogen‐containing contraception for women with migraine with aura. Only 37.3% (41/110) of respondents reported having headache/migraine education. Providers indicated interest in education pertaining to migraine prevention and treatment (96.3%; 105/109), migraine‐associated disability (74.3%; 81/109), and diagnostic testing (59.6%; 65/109). Conclusion: Women's healthcare providers appear to have several knowledge gaps regarding the management of migraine in their patients. These providers would likely benefit from access to a headache‐specific educational curriculum to improve provider performance and patient outcomes.